Incumplimiento del derecho constitucional de acceso a la información pública en la provincia de El Oro. - De la Cruz Palas, Melissa Rocío (2018)
The present case N ° 07317-2017-00352 deals with the breach of the jurisdictional guarantee as it is the access to public information in which the actor establishes Mr. NN and as defendant the Syndic Attorney of the MUNICIPAL GAD OF CANTON EL GUABO and the MUNICIPAL RECORDER OF THE CANTON EL GUABO PROPERTY. The plaintiff asks the property registrar for a certificate of ownership of a property already canceled, of his property that is circulating through social networks, and to be informed who authorized the publication of the certificate and not having an answer to your request Interposes an action of access to public information against the property registrar and the Municipality of the Canton of Guabo and consequently to the Syndic Attorney who alleges that this certificate is not conferred, because the applicant abruptly entered the public entity without respecting the staff that was in the offices and request the request in a prepotent manner and demonstrating its physical size before this demand the party filed presents a certification of the property but does not inform with what authorization the public therefore, according to what the law establishes, the action of access to public information is intended to guarantee access to public information, when it has been expressly or tacitly denied, when it is believed that the information provided is not complete or has been altered or when physical access to the sources of information has been denied, the action will also proceed when the denial of the information is based on the secret or reserved nature of the same reason why we are analyzing a violation before the present constitutional guarantee for reason that is considered incomplete to public information.